2010
DOI: 10.7763/ijesd.2010.v1.34
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Spentwash Application on Nitrogen Dynamics in Soil

Abstract: Distillery spentwash contains all nutrients and organic matter and used in agriculture as a source of plant nutrients and irrigation water. Besides all the nutrients, spentwash contains appreciable amount of nitrogen also. The effect of different levels and methods of spentwash application on soil nitrogen dynamics was examined through a field experiment. The field experiment was conducted using Groundnut (Arachis hypogea L.) as a test crop. At all stages of groundnut growth, the amounts of NH 4-N and NO 3-N w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
(6 reference statements)
2
4
0
Order By: Relevance
“…Further, its relative influence compared to other wastewaters is appreciable in red soil compared to other three soils. Similar findings were reported in sewage-treated soils [30]; bio-methanated spentwash-treated soil [23] reported that continuous application of different levels of spentwash had remarkably increased the NH 4 -N in soil. Both ammoniacal nitrogen content and nitrate nitrogen content were highest in lateritic soil with all other soils coming together as second.…”
Section: Ammoniacal Nitrogensupporting
confidence: 86%
See 1 more Smart Citation
“…Further, its relative influence compared to other wastewaters is appreciable in red soil compared to other three soils. Similar findings were reported in sewage-treated soils [30]; bio-methanated spentwash-treated soil [23] reported that continuous application of different levels of spentwash had remarkably increased the NH 4 -N in soil. Both ammoniacal nitrogen content and nitrate nitrogen content were highest in lateritic soil with all other soils coming together as second.…”
Section: Ammoniacal Nitrogensupporting
confidence: 86%
“…The nitrate concentration was observed higher at surface layer (0-15 cm) in all the soils at different pore volumes passage and decreased steadily with depth. Continuous application of different levels of spentwash had remarkably increased in the NO 3 -N in soil [23]. Like carbon fractions, nitrogen fractions also recorded higher at surface layer in all the soils under different treatments.…”
Section: Nitrate Nitrogenmentioning
confidence: 84%
“…As the quantity of PBSW was increased, the available N content in soil was decreased in all the three soil depths. This might be due to high COD and BOD of PBSW which resulted in immobilization of available N. The high COD and BOD can increase the temperature and immobilize the nutrients particularly N as well as depletion of oxygen in soil (Kalaiselvi and Mahimairaja, 2010). Available phosphorus: The highest pooled available P content in soil (16.21, 15.11 and 12.18 kg ha -1 ) was recorded in treatment T 4 (50% N-PBSW and remaining N and P -chemical fertilizers) at all the soil depths.…”
Section: Resultsmentioning
confidence: 99%
“…The control recorded the least value (92 kg ha -1 ). Kalaiselvi et al (2010) reported that higher N availability in DSW applied soil could be due to the direct contribution of nitrogen as well as increased microbial activity due to the added organic matter. ) of soil at different incubation periods and nitrogen levels on the NO3-N concentration of soil sampled at 15-day intervals during the incubation period.…”
Section: Ammonical-nitrogen (Nh 4 -N)mentioning
confidence: 99%